The T-Cell Receptor β Variable Gene Promoter Is Required for Efficient Vβ Rearrangement but Not Allelic Exclusion - Ryu, Chun Jeih (American Society for Microbiology, 2004)
To investigate the role of promoters in regulating variable gene rearrangement and allelic exclusion, we constructed mutant mice in which a 1.2-kb region of the Vβ13 promoter was either deleted (P13(−/−)) or replaced with the simian virus 40 minimal promoter plus five copies of Gal4 DNA sequences (P13(R/R)). In P13(−/−) mice, cleavage, rearrangement, and transcription of Vβ13, but not the flanking Vβ gene segments, were significantly inhibited. In P13(R/R) mice, inhibition of Vβ13 rearrangement was less severe and was not associated with any apparent reduction in Vβ13 cleavage. Expression of a T-cell receptor (TCR) transgene blocked cleavages at the normal Vβ13-recombination signal sequence junction and Vβ13 coding joint formation of both wild-type and mutant Vβ13 alleles. However, a low level of aberrant Vβ13 cleavage was consistently detected, especially in TCR transgenic P13(R/R) mice. These findings suggest that the variable gene promoter is required for promoting local recombination accessibility of the associated Vβ gene segment. Although the promoter is dispensable for allelic exclusion, it appears to suppress aberrant Vβ cleavages during allelic exclusion.